PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, ORGANIZATIONAL JUSTICE DAN PROCEDURAL JUSTICE TERHADAP JOB SATISFACTION PADA KARYAWAN PACTO BALI PRIMA - Ardikayasa, I Gede Sumar; Suwandana, I Gusti Made (E-Jurnal Manajemen; Vol 7 No 9 (2018)DO - 10.24843/EJMUNUD.2018.v07.i09.p09, 2018)
This study aims to determine the Influence of Transformational Leadership, Organizational Justice, and Procedural Justice on Job Satisfaction in Pacto Bali Prima employees. Transformational Leadership, Organizational Justice, and Procedural Justice need to be considered to grow Job Satisfaction from employees. This research was conducted on all employees in Pacto Bali Prima. Samples taken are as many as 65 employees. Sampling technique using saturated sampling (census) where the entire population is sampled. The analysis technique used is multiple linear regression analysis. The results of this study indicate that Transformational Leadership positively and significantly influence to Job Satisfaction, Organizational Justice have positive and significant influence to Job Satisfaction and Procedural Justice have positive and significant influence to Job Satisfaction at Pacto Bali Prima.Manajer company must keep and always pay attention to how big Transformasional Leadership, Organizational Justice and Procedural Justice perceived by its employees. It aims to create employees who have Transformational Leadership, Organizational Justice and Procedural Justice attitude toward employees at Pacto Bali Prima. Keywords: Transformational Leadership, Organizational Justice, Procedural Justice, Job Satisfaction